Increased Exercise Effort after Artificially-Induced Stress: Laboratory-Based Evidence for the Catharsis Theory of Stress (Baltic Journal of Sport and Health Sciences, 2020)
Background. Evolution prepared humans to deal with physical challenges. Today, people encounter psychosocial stress more than physical stress. However, the physiological response to the contemporary forms of stress is still preserved as the biological evolution’s vestigial heritage. This laboratory investigation aimed to determine whether brief mental stress triggers greater innate (instinctual) effort to ‘let off steam’ than a non-challenging control condition.Method. Using a counterbalanced within-participants laboratory design, 29 young men walked/jogged at voluntary (self-paced) effort after two conditions: a) artificially-induced mental stress comprised by the Stroop Color-Word Task, which lasted for five minutes, and b) a control session, also lasting for five minutes, in which the participants watched a video depicting the world’s ten tallest buildings.Results. The increased arousal after mental stress was carried over into the walk or jog period, and participants worked harder, but they did not perceive exerting greater effort in contrast to the control condition.Conclusions. These results suggest that a ‘flight or fight’ response to psychosocial stress is manifested in the form of subliminal catharsis. While larger-scale studies with more impactful stressors are needed, these preliminary results support the catharsis theory. They might open new research avenues to provide people more physical opportunities for letting off steam before the necessity of treatment with chemical substances or other behavioral therapies.Keywords: cognitive stress, exercise, mental stress, flight or fight, physical activity, psychosocial stress.